IMPLEMENTASI PROGRAM ZAKAT PRODUKTIF TERHADAP KESEJAHTERAAN MUSTAHIK PADA MASA PANDEMI COVID-19 (Studi Kasus BAZNAS Kab.Cirebon) - Yusuf Paisal; Ayu Risalah; Siti Nila Rokhmana (Al Naqdu, 2021)
One of the efforts to alleviate poverty is to utilize zakat for productive businesses. This study aims to determine the effect of productive zakat on the level of the economy or the welfare of mustahik during the Covid-19 period by BAZNAS Cirebon Regency, and how to review the sharia economy. This type of research is a qualitative research with interview research methods, observation and documentation. Interviews were conducted with Baznas Cirebon district as the party authorized to collect and distribute zakat. The utilization of zakat for productive businesses is also divided into several forms, namely business capital in the form of money, production equipment, business loans, and training that supports entrepreneurship. This aims to optimize and maximize in running their business in accordance with the needs and business continuity of mustahik as the party who gets this productive zakat.